Habitat heterogeneity drives the host‐diversity‐begets‐parasite‐diversity relationship: evidence from experimental and field studies. (5th May 2016) - Johnson, Pieter T. J.; Wood, Chelsea L.; Joseph, Maxwell B.; Preston, Daniel L.; Haas, Sarah E.; Springer, Yuri P.
Abstract: Despite a century of research into the factors that generate and maintain biodiversity, we know remarkably little about the drivers of parasite diversity. To identify the mechanisms governing parasite diversity, we combined surveys of 8100 amphibian hosts with an outdoor experiment that tested theory developed for free‐living species. Our analyses revealed that parasite diversity increased consistently with host diversity due to habitat (i.e. host) heterogeneity, with secondary contributions from parasite colonisation and host abundance. Results of the experiment, in which host diversity was manipulated while parasite colonisation and host abundance were fixed, further reinforced this conclusion. Finally, the coefficient of host diversity on parasite diversity increased with spatial grain, which was driven by differences in their species–area curves: while host richness quickly saturated, parasite richness continued to increase with neighbourhood size. These results offer mechanistic insights into drivers of parasite diversity and provide a hierarchical framework for multi‐scale disease research.